The outcomes book : debate and consensus after the WPA outcomes statement - Harrington, Susanmarie (Utah State University Press, 2005)
The WPA Outcomes Statement is important because it represents a working consensus among composition scholars about what college students should learn and do in a composition program. But as a single-page document, the statement cannot convey the kind of reflective process that a writing program must undertake to address the learning outcomes described.